Caracterização metamórfica do Greenstone Belt de Guarinos - GO - Lima, Filipe Goulart [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The study area comprises Guarinos Greenstone Belt which is located in the centralwest state of Goias and has an approximate size of 280 km2. The present work has as main objective to characterize the metamorphism of the greenstone belt and the relationship between the tectonic events and the metamorphism. For the execution of the work we used data collected in the course Geological Mapping of Crystalline Area of the geology course of UNESP, classes 2009 and 2010, the data collected by Alex Choupina Joaquim Andrade Silva in his master's thesis and the information collected in field in the study area. This compilation of data allows approximately 200 thin sections have been evaluated and allowed the construction of the metamorphic map in scale 1:125.000, also allowed the preparation of the geological map in scale 1:125.000 greestone belt, based on 1:25.000 scale maps performed by students of UNESP and the mapping conducted by Silva (2011). The study area was divided into two tectonic compartments depending on the Shear Zone Engenho Velho that longitudinally crosses study area, with direction approximately NW-SE. The west compartment is bordered by granite-gneiss complex and the east compartment, seems thicker to the south and narrows gradually towards the north and its structure is seen in general as a great monoclinal with NW-SE direction with trim to SW, this way your stack was considered as a package of rocks at the base and metaultramafic metamafic the top, with a second package in tectonic contact, which is composed of detrital and chemical metasedimentary rocks. The east compartment is represented by the intrusion of a large granitic body surrounded by amphibolites and metasediments, is bounded on the east by a granite-gneiss complexes through thrust fault, and is bounded on the west by the other compartment. The structure of the compartment is seen as a major axis oriented roughly... (Completo abstract click electronic access below)

A área de estudo compreende o Greenstone Belt de Guarinos que se localiza na porção centro-noroeste do Estado de Goiás e possui uma dimensão aproximada de 280 km2. O presente trabalho tem como principal objetivo a caracterização metamórfica do greenstone belt e a relação dos eventos tectônicos com o metamorfismo. Para a execução do trabalho foram utilizados os dados levantados na disciplina “Mapeamento Geológica de Áreas Cristalinas” do curso de Geologia da UNESP, turmas 2009 e 2010, os dados levantados por Alex Joaquim Choupina Andrade Silva em sua tese de mestrado e as informações coletadas em campo na área de estudo. Essa compilação de dados forneceu cerca de 200 lâminas delgadas que foram avaliadas, a confecção do mapa metamórfico na escala 1:125.000, e a confecção do mapa geológico do greestone belt na escala 1:125.000, baseado nos mapeamentos em escala 1:25.000 realizados pelos alunos da UNESP no mapeamento realizado por Silva (2011). A área de estudo foi dividida em dois compartimentos tectônicos em função da Zona de Cisalhamento Carroça que a atravessa longitudinalmente, com direção aproximadamente NW-SE. O compartimento oeste é limitado por complexos granito-gnáissicos e pelo compartimento leste, mostra-se mais espessa ao sul e estreita-se gradualmente em direção ao norte e sua estruturação é tida, em geral, como uma grande monoclinal com direção NW-SE com caimento para SW, desta maneira seu empilhamento foi considerado como um pacote de rochas metaultramáficas na base e metamáficas no topo, sotoposto por um segundo pacote, em contato tectônico, que é composto por rochas metassedimentares químicas e detríticas. O compartimento leste é representado pela intrusão de um grande corpo granítico circundado por anfibolitos e metassedimentos, é limitado a leste por um dos complexos granítico-gnáissicos através de falha de empurrão... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Metamorfismo (Geologia); Paragenese; Rochas metamorficas; Facies (Geologia); Anfibolito; Guarinos (GO); Metamorphism (Geology); Paragenesis; Greenstone belts; Metamorphic rocks; Facies (Geology); Amphibolite